Sistem, Paradigma dan Dinamika Pesantren sebagai Pendidikan Islam Alternatif - Abd. Muqit (Program Pascasarjana Universitas Ibrahimy, 2019)
The system of education in pesantren becomes necessary, because it makes a set of interrelated, interdependent and strengthen one another to achieve the goals of education in pesantren, those are to form a democratic, competitive, innovative, and good society not only in science and technology (IPTEK), but also in iman and taqwa (IMTAQ), and to be responsible and have a good moral. Pesantren has a strong influence on almost all aspects of rural society life. The development of religious thought and interpretation from outside elite of pesantren did not have a significant impact on the way of life and attitudes of rural society. This fact shows that every effort aimed at society development, especially in rural area, needs to implicate pesantren. As time goes by, pesantren combines religious education and general education, which can produce the religious experts (ilmiah-amaliah-diniah) relevant to the needs and demands of the times. It makes education in pesantren as an alternative and excellent education.